Development of Low-Shrink Epoxy Putty to Solve Appearance-Quality Defects of Carbon-Fiber-Reinforced Plastic Automotive Exterior Parts - Manseok Yoon (MDPI AG, 2021)
In this study, epoxy putties with novel compositions were developed for the filling of structural voids in carbon-fiber-reinforced plastics (CFRPs), which are used to fabricate automotive parts. Two constituent solutions—one consisting of epoxy resins and the other consisting of a hardener—were formulated, mixed, and then coated on CFRP surfaces, followed by curing. The surfaces were then evaluated to determine the shrinkage rates (calculated based on the liquid densities and cured mixtures), adhesion properties (determined by a peel test), and color differences (measured with a colorimeter) of the synthesized putties. The last two properties were compared with those of the commercially available putties to ascertain the thermal resistance of the developed putties. The results indicated that the synthesized epoxy putties were more strongly adhesive and exhibited less difference in color. Furthermore, after thermal impact, both the adhesive properties and color stabilities of the synthesized epoxy putties were found to be superior to those of the commercial putty.